2012
DOI: 10.1142/s0219091511500081
|View full text |Cite
|
Sign up to set email alerts
|

Value Relevance Change Under International Accounting Standards: An Empirical Study of Peru

Abstract: In face of broad adoption of International Financial Reporting Standards (IFRS), the Securities and Exchange Commission (SEC) is considering its quality and acceptability. This paper reports a study that examines changes in value relevance with a sample of Peru firms mandated to use international accounting standards between 1999 and 2007. The period under study is broken into a period of International Accounting Standards (IAS) between 1999 and 2001, a period of early IFRS between 2002 and 2004, and a more re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
2
6
1
2
Order By: Relevance
“…A study of the Cypriot market was motivated by similar concerns and reported results rather similar to our own (see Vafeas et al, 1998). Liu et al (2012) present evidence of the effect of international financial reporting standards (IFRS) compliance on the value relevance of earnings in Peru. Here, we focus on the PEAD anomaly in the Greek market in a era of radical accounting change and report a resurgence in PEAD compared to that observed in an immediately prior period.…”
Section: Introductionsupporting
confidence: 76%
“…A study of the Cypriot market was motivated by similar concerns and reported results rather similar to our own (see Vafeas et al, 1998). Liu et al (2012) present evidence of the effect of international financial reporting standards (IFRS) compliance on the value relevance of earnings in Peru. Here, we focus on the PEAD anomaly in the Greek market in a era of radical accounting change and report a resurgence in PEAD compared to that observed in an immediately prior period.…”
Section: Introductionsupporting
confidence: 76%
“…contrary to the research by Liu et al (2012), this paper reaches a different conclusion regarding the value relevance of accounting numbers in the period following the early adoption of IFRS in Peru: there is high value relevance not only in the early IFRS adoption period, but also in the period after 2004.…”
Section: Datacontrasting
confidence: 99%
“…Findings: This paper studied the value relevance of accounting figures in the Lima Stock Exchange between 1994 and 2012. On one hand, it complements previous studies by Ndubizu and Sanchez (2006), Liu et al (2012), andMartínez, P. et al (2012), which covered different periods (from 1994 to 1999 for the first one, 2002 to 2009 for the second, and from 1999 to 2007 for the latter). On the other hand,…”
Section: Datasupporting
confidence: 88%
“…Relevant accounting information from different sources, including financial statements, can alter users’ investment and credit decisions (Deegan, 2016; Krause and Tse, 2016; Comiran et al , 2018). Hence, the VR of accounting information can be assessed by the financial statements’ capacity to capture information that significantly influences a firm’s equity value (Francis and Schipper, 1999; Liu et al , 2012; Cheng et al , 2013). The development of the stock markets needs relevant accounting information, that is useful and effective in decision making (Ji et al , 2015; Chen et al , 2016).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%